Successful case of using suture-mediated system Perclose ProGlide in TAVI - B. M. Todurov; M. B. Todurov; A. V. Khokhlov; M. V. Stan; K. L. Berestova; O. V. Zelenchuk; A. V. Besaga; S. R. Maruniak (Кардіохірургія та інтервенційна кардіологія)
Transcatheter aortic valve implantation (TAVI) has changed the treatment approach for patients with critical aortic stenosis. This clinical case describes the performance of TAVI in a patient with liver cirrhosis, autoimmune hepatitis, coagulopathy, and secondary anemia. Particular attention was paid to complications in the postoperative period. It was necessary to reduce the risks of bleeding and traumatization of blood vessels due to coagulopathy, therefore, to choose a low-traumatic method of closing the postoperative wound and start early activation of the patient in the postoperative period.